Examining Digital Competence among Filipino Public School Teachers: Generational Gaps, Institutional Support and ICT Perceptions - Wong, Amaranth; Sy, Feluz Irish; Wong, Jonathan (Journal of Interdisciplinary Perspectives, 2025)
This study examines the digital competence of public elementary school teachers in the Romblon District, Philippines, with a focus on generational differences, support for capacity building, and attitudes toward technology use in education. Addressing the growing need for teacher readiness in digital classrooms, the study used a descriptive-correlational research design with 296 participants. Teachers were grouped as digital natives (born after 1980) and digital immigrants (born before 1980). Findings showed that digital natives demonstrated higher levels of digital competence compared to digital immigrants. Teachers who reported greater access to training, technology resources, and peer collaboration also had stronger digital skills. Additionally, a positive attitude toward ICT integration was linked to higher competence. These results suggest that institutional support and teacher mindset play essential roles in developing digital proficiency. The study recommends targeted training programs based on generational needs, equal access to digital resources, and stronger peer learning communities. These strategies can help bridge gaps in digital competence and enhance the overall integration of technology in teaching. The findings contribute to ongoing efforts to improve teacher preparedness for digital education in both local and global contexts.